Mechanisms, assessment and therapeutic implications of lung hyperinflation in COPD. Issue 7 (July 2015) - Rossi, Andrea; Aisanov, Zaurbek; Avdeev, Sergey; Di Maria, Giuseppe; Donner, Claudio F.; Izquierdo, José Luis; Roche, Nicolas; Similowski, Thomas; Watz, Henrik; Worth, Heinrich; Miravitlles, Marc
Summary The main complaint of patients with chronic obstructive pulmonary disease (COPD) is shortness of breath with exercise, that is usually progressive. The principal mechanism that explains this symptom is the development of lung hyperinflation (LH) which is defined by an increase of functional residual capacity (FRC) above predicted values. Patients with COPD may develop static LH (sLH) because of destruction of pulmonary parenchyma and loss of elastic recoil. In addition, dynamic LH (dLH) develops when patients with COPD breathe in before achieving a full exhalation and, as a consequence, air is trapped within the lungs with each further breath. Dynamic LH may also occur at rest but it becomes clinically relevant during exercise and exacerbation. Lung hyperinflation may have an impact beyond the lungs and the effects of LH on cardiovascular function have been extensively analysed. The importance of LH makes its identification and measurement crucial. The demonstration of LH in COPD leads to the adoption of strategies to minimise its impact on the daily activities of patients. Several strategies reduce the impact of LH; the use of long-acting bronchodilators has been shown to reduce LH and improve exercise capacity. Non pharmacologic interventions have also been demonstrated to be useful. This article describes the pathophysiology of LH, its impact on the lungs and beyond and reviews the strategies that improve LH in COPD.